Pemberdayaan keluarga pada balita gizi kurang dalam pengolahan menu untuk pencegahan stunting di Kelurahan Karang Asam Ilir Kota Samarinda - Wahyuni, Rahmawati; Syukur, Nursari Abdul; Suryani, Heni (Politeknik Kesehatan Kemenkes Aceh, 2024)
Low attendance of toddlers at the Posyandu in Karang Asam Ilir, Samarinda, affects the monitoring of child development, with 45 malnourished toddlers and 2 suffering from severe malnutrition in 2022. Educational and demonstration programs on menu preparation were implemented to empower families and health cadres in preventing stunting. Results showing increased knowledge and skills of mothers and health cadres regarding high-calorie menu preparation. Conclusion is family empowerment and education effectively improved knowledge and skills in stunting prevention.